Direct conservation payments in the Brazilian Amazon: Scope and equity implications - Borner, J.; Wunder, Sven; Wertz-Kanounnikoff, Shiela; Tito, M.R.; Pereira, L.S.; Nascimento, N. (2010)
This article looks into the scope and equity implications of applying payments for environmental services (PES) as a REDD implementation mechanism in the Brazilian Amazon. We establish a set of economic and institutional preconditions for PES to become a feasible and cost-effective conservation mechanism. We proceed with a macro-scale spatial analysis and overlay of opportunity costs, deforestation patterns, carbon services, and land tenure, in order to assess where these conditions hold. We then screen how the benefits of potential PES schemes might be distributed across different socioeconomic groups of service providers in different land tenure categories. Our economic–quantitative analysis, though sensitive to documented assumptions, suggests that under current carbon prices the economic preconditions are in place to pay for avoided deforestation in over half of threatened forests over the next decade. Unfortunately, the same optimism does not apply to institutional preconditions. Land grabbing, insecure tenure, overlapping claims, and lacking information on private tenure constitute real medium-term impediments to PES. If payments were to accrue to current landholders regardless of current tenure insecurities, large landowners who account for about 80% of all deforestation would reap the highest benefits, though per-capita benefits other tenure categories are also high. Schemes that closely align payments with opportunity costs are preferable for cost-effectiveness, and not necessarily more inequitable in outcomes. Essentially, PES systems cannot substitute command-and-control measures: the former depend on the latter for basic governance systems to secure effective rights of exclusion, which land stewards essentially need in order to become reliable service providers.